La precariedad laboral en la inserción de los jóvenes en el mercado laboral latinoamericano (2020)
The present degree work is focused on addressing the social and economic problems generated by job insecurity in Latin America based on studies conducted with the young population, it is taken into account that currently the least favored workers in terms of a stable work environment We are young people, so the importance of studying, analyzing and understanding the causes and consequences in respect to the precariousness implanted by organizations. This analysis is carried out in order for governments to try to impart laws based on such advanced studies and, with this, to ensure that the airlines and internal airlines of each country change the way they treat their workers and understand the importance that if an employee He is happy in his load and comes to acquire a sense of belonging to the company, the probability that it will be a successful company will be higher following good practices with its employees, providing them with a better quality of life in their workplace and thus generating its productivity continues and exponential, which in itself is the purpose of each organization.